Research on Shield Tunnelling Parameters Correlation in Composite Strata - Ziqi Guo; Huipeng Zhang; Xiaoyang Shi; Zhi Huang; Yiyong Xu; Zhiqiang Zhang (Advances in Materials Science and Engineering)
Shield tunnelling has become the development direction of tunnel construction due to its safety, economy, and speed. The complex formation has complicated geological changes, including soft rock, hard rock, and soft and hard inhomogeneous formation. It is particularly difficult to select and control the tunnelling parameters in shield tunnelling, while the reasonable selection and control of the tunnelling parameters play an important role in the excavation efficiency, tool wear, and surface settlement. Based on the tunnel project between the Dinggong Road North Station and the People’s Park Station online 4 of Nanchang Metro during shield tunnelling construction, this paper collects thrust, torque, and revolution speed of the cutterhead during shield tunnelling in the complex strata with differentiated argillaceous siltstone and gravel and analyzes these parameters by means of mathematical statistics analysis, in order to explore the interrelationship between shield tunnelling parameters under different stratigraphic conditions and put forward optimization suggestions for tunnelling parameters, which can provide a reference for control of tunnelling parameters of earth pressure shield in composite strata.